Prospects of Development of the Metaverse: Empirical Evidence - A. S. Yukhno; H. S. Umarov (Управленческое консультирование)
The purpose of the research is to analyze the key features of the metaverse, the possibilities and advantages of its tools, security issues and the format of user participation in the metaverse virtual space. The relevance of the study is caused by the changes in the global economic order and the metaverse technologies awareness from both the expert community and ordinary users. The authors use methods of comparative analysis of Russian and foreign scientific sources, as well as statistical analysis and forecasting from leading consulting, rating and analytical agencies (Gartner, Statista, Emergenresearch, Moscow Innovation Agency, World Economic Forum, Tadviser). The scope of the achieved results is determined by the possibility of using the practical part of the study in building scenarios for the metaverse technologies application by various stakeholders. The authors draw conclusion that there is a wide range of use of the metaverse tools in various felds of human activity (professional, educational, social, entertainment, etc.), as well as about stimulating the development of the digital market using metaverse technologies. The prospects of non-interchangeable tokens, one of the innovative tools of the metaverse, are discussed and the audience growth rate of the metaverse innovative technologies potential consumers in the future is predicted.